2001
DOI: 10.1101/gr.gr-1677rr
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variability of a Human Pseudogene

Abstract: We have obtained haplotypes from the autosomal glucocerebrosidase pseudogene (psGBA) for 100 human chromosomes from worldwide populations, as well as for four chimpanzee and four gorilla chromosomes. In humans, in a 5420-nucleotide stretch analyzed, variation comprises 17 substitutions, a 3-bp deletion, and a length polymorphism at a polyadenine tract. The substitution rate on the pseudogene (1.23 ± 0.22 × 10 −9 per nucleotide and year) is within the range of previous estimates considering phylogenetic estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 33 publications
1
40
0
2
Order By: Relevance
“…Although in principle, at each position of a sequence stretch, any of the four possible nucleotide bases can be present, SNPs are usually biallelic in practice. One of the reasons for this, is the low frequency of single nucleotide substitutions at the origin of SNPs, estimated to being between 1 × 10 −9 and 5 × 10 −9 per nucleotide and per year at neutral positions in mammals [48,57]. Therefore, the probability of two independent base changes occurring at a single position is very low.…”
Section: Definition Of Snps and The Generation Of Single Nucleotide Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in principle, at each position of a sequence stretch, any of the four possible nucleotide bases can be present, SNPs are usually biallelic in practice. One of the reasons for this, is the low frequency of single nucleotide substitutions at the origin of SNPs, estimated to being between 1 × 10 −9 and 5 × 10 −9 per nucleotide and per year at neutral positions in mammals [48,57]. Therefore, the probability of two independent base changes occurring at a single position is very low.…”
Section: Definition Of Snps and The Generation Of Single Nucleotide Pmentioning
confidence: 99%
“…Also, the much higher mutation rate of microsatellites, estimated to be as high as 1 × 10 −5 [42] when compared to the 1 × 10 −9 for SNPs [48,57], can be a concern, especially for association and linkage disequilibrium studies.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…In addition, a polymorphic CT repeat (5GC3.2) 3.2 kb upstream and a tetranucleotide AAAT repeat (ITG6.2) 9.8 kb downstream of GBA have been identified [Lau et al, 1999]. Variation in the GBA pseudogene includes 17 single-nucleotide substitutions, a three-nucleotide deletion, and a polyadenine tract [Martinez-Arias et al, 2001a. These polymorphisms in GBAP are important in the recognition of GBAP to GBA gene conversion events [Martinez-Arias et al, 2001b].…”
Section: Polymorphismsmentioning
confidence: 99%
“…Metaxin also has a pseudogene, which is located in the 16-kb region between GBA and GBAP. Both pseudogenes appear to have resulted from a duplication of the region, and are present in primates, but not in other species [Martinez-Arias et al, 2001a;Winfield et al, 1997]. The sequences of both GBA and MTX1 have been shown through multispecies comparative sequence analyses [Thomas et al, 2003] to have conservation of the exonic regions in humans and nine mammalian species [LaMarca et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we find that the analyses of pseudogenes (Li and Tanimura 1987;Nachman and Crowell 2000;Martinez-Arias et al 2001) and introns (Bergstrom et al 1999;Chen et al 2001) have produced much lower estimates of evolutionary divergence than those observed in synonymous sites in protein coding genes (Li and Tanimura 1987;Wolfe et al 1989;Easteal 1991;Keightley and Eyre-Walker 2000;Duret et al 2002;Kumar and Subramanian 2002). Also, intergenic DNA (excluding regulatory sites), which is expected to mutate at a rate similar to that for the coding DNA, also consistently shows much smaller evolutionary divergences than those obtained from coding sequences (Bohossian et al 2000;Zhao et al 2000;Chen et al 2001;Mathews et al 2001;Yu et al 2001).…”
mentioning
confidence: 99%